Spatiotemporal variability in the feeding habits of anchovy and sardine: a comparison of upwelling and river-runoff driven ecosystems - Rumolo, Paola; Barra, Marco; Bonanno, Angelo; Altieri, Simona; Ferreri, Rosalia; Gargano, Antonella; Basilone, Gualtiero; Gherardi, Serena; Genovese, Simona; Di Cicco, Maria Rosa; Lubritto, Carmine (Frontiers in Marine Science, 2025)
European sardine (Sardina pilchardus) and anchovy (Engraulis encrasicolus) are important components of marine food webs, acting as trophic links between primary consumers and higher trophic levels. However, local factors—such as environmental conditions, human activities, coastal pollution, and more generally, climate change have had a significant impact on their trophic interactions, affecting the energy flow, structure, and function of the marine ecosystems in which they live. Although both species are among the most explored in the Mediterranean Sea, due to their commercial and ecological importance, the spatiotemporal variability in their trophic ecology is still poorly addressed, particularly when combining life stage, sampling year, and geographic location. Here, we propose a spatio-temporal analysis of the trophic variability of juvenile and adult anchovy and sardine in two different areas of the central Mediterranean Sea—the Tyrrhenian Sea (TR) and the Strait of Sicily (SS)—over 4 years (2011, 2014, 2015, and 2017). We used a stable isotope (δ13C and δ15N) approach to assess variability in feeding behaviour and isotopic niche metrics (niche width and overlap) across space and time. The two study areas are influenced by different water masses with distinct physical and biological properties, leading to local changes in the marine food web and consequently in the feeding behaviour of both fish species at different life stages. In all sampled years, higher δ15N and δ13C values were found in both anchovy and sardine sampled in the Tyrrhenian Sea (mean values: 8.8‰ and −17.5‰ for anchovy; 9.5‰ and −18.1‰ for sardine) compared with those from the Strait of Sicily (mean values: 6.6‰ and −18.9‰ for anchovy; 6.8‰ and −19.0‰ for sardine). Furthermore, the higher δ¹5N values observed indicate no significant relationship between isotopic values and organism size. Our results support the hypothesis that the higher isotopic signals observed in both juvenile and adult anchovy and sardine in the Tyrrhenian Sea may be linked to higher trophic-level food sources (e.g., predation on large prey such as krill), potentially associated with persistent local features (e.g., submarine canyons). Moreover, the greater number of cases showing wider isotopic niches and higher isotopic overlap between species—and between life stages—in the Tyrrhenian Sea than in the Strait of Sicily suggests higher variability in feeding behaviour and access to more diversified food sources. These data contribute to a better understanding of food web dynamics and may be used to improve ecosystem models, which requires an understanding of the ecological processes that control the interaction between species.